Autism childhood and beyond - Film For The Humanities & Sciences (Firm) (Princeton, New Jersey : Film For The Humanities & Sciences, 2004)
This program examines the therapies currently in use or under study: drugs, sing language, and the highly controversial aversive therapy. The program profiles a 26-year-old autistic man whose amazing mathematical abilities contradict his low-to-normal IQ of 90
DVD format
Keywords: Autism; Autism in children